Analisis Faktor Penyebab Tingginya Angka Cerai Gugat di Pengadilan Agama Sumber Kelas 1A - layyaazzahwa layya; Asep Kamaludin; Amalia; Masyhari (Al Naqdu, 2021)
The increasing number of divorce cases in the Sumber Religion Court Class 1A in 2021, especially divorce lawsuits is a problem that needs attention because it is not in accordance with the purpose of marriage. The results of the study indicate that the cause of the high rate of divorce is due to various factors that affect domestic life, including economic factors, continuous disputes and quarrels, leaving one party behind, and other factors. The solution needed to overcome this is to provide training and learning to the younger generation or couples who want to marry so that they understand the laws and regulations of marriage so that there will be no disharmony in the household in the future.